Formation of Dihydroxystearic Acid (DHSA) from epoxidized palm oleic acid by peracid mechanism and their kinetic study / Mohd Jumain Jalil...[et al.] - Jalil, Mohd Jumain; Habr, Hamzah Hafizuddin; Abdul, Hadi; Mohd Yamin, Aliff Farhan; Ismail, Kamariah Noor; Abdul Rani, Noor Hidayu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Dihydroxystearic acid (DHSA) is a product derived from a chemical modification of palm oleic acid. Application of these valuable fatty acids can be found in cosmetics, as a thickening agent and as a coating agent for pigments due to its unique structure. This study investigates the effect of a catalyst on epoxidation and the formation of DHSA by peracid mechanism. The epoxidation yield calculated by relative conversion to oxirane (RCO%) with a high yield of 95% achieved. Thereafter, the epoxidized oleic acid was hydrolyzed to produce DHSA. The formation of DHSA was verified by analysed the physicochemical properties using Fourier Transform Infra-red (FTIR). The kinetic model was being conducted to determine reaction rate using Particle Swarm (PS). The result showed that PS obtained a minimum error of 0.2005 and a correlation coefficient, r of 0.9999.